Community Engagement in Climate Change: Models of Culturally Appropriate Citizen Science: Theorizing From the Literature - Lisa Baumgartner; JIll Zarestky (Adult Education Research Conference, 2017)
Climate change is increasingly affecting people in rural and indigenous communities. This paper explores opportunities for adult educators to develop and support community programs related to environmental change and preservation.
Keywords: climate change; community education; environmental education